Pengaruh Kinerja Kepala Madrasah dan Kinerja Guru terhadap Mutu Lulusan Siswa - Asrop Safi'i (LP. Ma'arif Janggan Magetan, 2023)
The quality of graduate students at the SMA/MA level is not optimal when viewed from the national exam scores which are not included in the top five categories with the highest scores in Indonesia. Madrasah heads and teachers within the scope of educational institutions are spearheads in creating quality graduates, so that in this study these two factors will be tested for their influence on graduate quality. The method in this study was a quantitative approach with the type of ex-post facto, with a population of all MAN teachers in Blitar district. While the sample was taken randomly from the three madrasas. Technical data analysis using simple and multiple regression tests with prerequisite tests for normality and linearity tests. From the results of this study, the authors concluded: 1) There is a positive and significant influence on the performance of madrasa principals on the quality of MAN student graduates in Blitar district by 49.8%. 2) There is a positive and significant effect of teacher performance on the quality of MAN graduate students in Blitar district by 53.5%. 3) There is an effect of the performance of madrasah heads and teachers' performance on the quality of MAN student graduates in Blitar district by 53.6%.